Health care services utilization and cost among residents of MT Solar I oil spill-affected coastal barangays in Guimaras - Ferrer, Alice Joan G. (Danyag : Journal of Humanities and Social Sciences, 2009)
This paper describes the pattern of utilization and cost of curative care using data on 2841 individuals from 615 households in 27 oil-spill affected barangays in Guimaras seven weeks after the incident. The household turned out to be the main provider of basic curative care. The medical mission and barangay health stations were the popular sources of care outside home. Individuals seeking care outside home spent more time on the road and waiting compared to actual time spent with health care provider. It is necessary to capacitate government facilities as they were highly used by individuals seeking care outside home. The transportation facilities in the area must also be improved to lower time cost of the people. Further study should look at health care utilization and cost months after oil spill. While the information provided in the present study are highly valuable, further analysis can be done not only to describe but also to explain choices of people regarding health care service utilization.